Clinical Efficacy of Percutaneous Kyphoplasty Combined with Calcitriol and Calcium in the Treatment of Traumatic Nonosteoporotic Vertebral Compression Fractures. (27th February 2022) - Dai, Shouqian; Lu, Xin; Dai, Ningning; Shi, Xiu; Yang, Peng; Peng, Peng; Xu, Feng
Abstract : Objective . The present study investigated the clinical efficacy of percutaneous kyphoplasty (PKP) combined with calcitriol and calcium in the treatment of traumatic nonosteoporotic vertebral compression fractures (TNVCFs). Methods . The patients were equally divided into a control group and a treatment group by a random number table. The patients in the control group underwent PKP surgery, and the patients in the treatment group received calcitriol and calcium on the basis of PKP surgery. The visual analog scale (VAS) pain scores, Oswestry Disability Index (ODI) scores, the height of the anterior edge of the vertebral body, Cobb's angle, and the level of the bone mineral density of the two groups of TNVCF patients before surgery were recorded and compared, one and six months after surgery. Results . Thirty-six inpatients with TNVCFs admitted to the trauma center of the First Affiliated Hospital of Soochow University from January 2019 to January 2020 were recruited. There were no significant differences in the VAS and ODI scores, the height of the anterior edge of the injured vertebral body, Cobb's angle, and bone mineral density between the two groups before surgery (P > 0.05 ). The VAS scores, ODI scores, the height of the anterior edge of the injured vertebral body, and Cobb's angle of the two groups of patients after surgery were significantly better than those before surgery. One and six months after surgery, the VAS and ODI scores, the height of the anterior edge of the injured vertebral body, Cobb's angle, and the bone mineral density of the patients in the treatment group improved significantly compared to those in the control group (P < 0.05 ). Conclusions . PKP combined with calcitriol and calcium medications could significantly relieve pain, alleviate the loss of compressed vertebral height and kyphosis, and improve the spinal function and the life quality of the TNVCF patients.